2018
DOI: 10.1038/s41598-018-20373-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular pathways and candidate genes associated with cocks’ comb size trait by genome-wide transcriptome analysis

Abstract: The comb of the male is an important secondary sexual characteristic. Although quantitative trait loci (QTLs) related to comb size have been identified, molecular mechanisms underlying this trait remain mostly unknown. In this study, RNA sequencing (RNA-seq) was employed to compare whole transcriptomic differences between two groups of Partridge Shank chickens that are divergent in comb sizes. A total of 563 differentially expressed genes (DEGs) were identified, including 277 up-regulated and 286 down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…More recently, RNA sequencing (RNA-seq) has become a powerful method for precise quantification of not only coding but also non-coding RNAs. With recent improvements of chicken genome information, RNA-seq successfully revealed the intriguing genes affecting egg albumen in layers 9 and comb size of cocks 10 . The latest studies using RNA-seq have also reported differential gene expression profiles in breast muscles of modern and foundation broiler lines 11,12 or those in broiler lines with high- and low-ultimate pH 13 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, RNA sequencing (RNA-seq) has become a powerful method for precise quantification of not only coding but also non-coding RNAs. With recent improvements of chicken genome information, RNA-seq successfully revealed the intriguing genes affecting egg albumen in layers 9 and comb size of cocks 10 . The latest studies using RNA-seq have also reported differential gene expression profiles in breast muscles of modern and foundation broiler lines 11,12 or those in broiler lines with high- and low-ultimate pH 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Each column represents a sample, and each row represents a gene. The red and blue gradients indicate an increase and a decrease in gene expression abundance, respectively ( Liu et al, 2018 ). (C) Venn diagram analysis showing the number of transcription factors targeting the PD-L1 promoter that can be affected by IFN-γ in HCT116 and HKE-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…This is not the only colour gene with a link with comb size, with the gene PIK3R1 also having prior links to comb size in chickens (Y. Liu et al, 2018).…”
Section: Feral Birds On Kauai and Bermudamentioning
confidence: 99%